2018
DOI: 10.1002/jmri.26343
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls in liver MRI: Technical approach to avoiding misdiagnosis and improving image quality

Abstract: The following is an illustrative review of common pitfalls in liver MRI that may challenge interpretation. This article reviews common technical and diagnostic challenges encountered when interpreting dynamic multiphasic T1‐weighted imaging, hepatobiliary phase imaging, and diffusion‐weighted imaging of the liver. Additionally, each section includes suggestions for avoiding diagnostic and technical errors. Level of Evidence: 5 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2019;49:41–58.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 100 publications
(289 reference statements)
3
10
0
Order By: Relevance
“…In line with our study, a lower ADC value was helpful for predicting MVI of HCC because theoretically it reflects higher tissue cellularity and decreased micro-capillary perfusion [9]. There are several pitfalls of DWI that could affect the reliability of the ADC measurement including [25,26]: (1) limited image quality with poor signal-to-noise ratio and low spatial resolution; (2) more sensitive to motion and air susceptibility, especially for pulsation artifacts in left robe; (3) misregistration artifacts on ADC map; (4) T2 blackout effect mainly due to fibrotic tissues or calcifications depicting hypointesity on both DW images and ADC maps. Some studies reported that the reproducibility for ADC and IVIM measurement of hepatic nodules was poor [27][28][29].…”
Section: Discussionsupporting
confidence: 78%
“…In line with our study, a lower ADC value was helpful for predicting MVI of HCC because theoretically it reflects higher tissue cellularity and decreased micro-capillary perfusion [9]. There are several pitfalls of DWI that could affect the reliability of the ADC measurement including [25,26]: (1) limited image quality with poor signal-to-noise ratio and low spatial resolution; (2) more sensitive to motion and air susceptibility, especially for pulsation artifacts in left robe; (3) misregistration artifacts on ADC map; (4) T2 blackout effect mainly due to fibrotic tissues or calcifications depicting hypointesity on both DW images and ADC maps. Some studies reported that the reproducibility for ADC and IVIM measurement of hepatic nodules was poor [27][28][29].…”
Section: Discussionsupporting
confidence: 78%
“…In line with our study, lower ADC value has been proven helpful for predicting MVI of HCC because it reflects higher tissue cellularity and decreased micro-capillary perfusion [9]. There are several pitfalls of DWI that affect the reliability of the ADC measurement including [21,22]: (1) limited image quality with poor signal-to-noise ratio and low spatial resolution; (2) more sensitive to motion and air susceptibility, especially for pulsation artifacts in left robe; (3) misregistration artifacts on ADC map;…”
Section: Discussionsupporting
confidence: 78%
“…In line with our study, a lower ADC value was helpful for predicting MVI of HCC because theoretically it reflects higher tissue cellularity and decreased micro-capillary perfusion [9]. There are several pitfalls of DWI that could affect the reliability of the ADC measurement including [25,26]: (1) limited image quality with poor signal-to-noise ratio and low spatial resolution; (2) more sensitive to motion and air susceptibility, especially for pulsation artifacts in left robe; (3) misregistration artifacts on ADC map; (4) T2 blackout effect mainly due to fibrotic tissues or calcifications depicting hypointesity on both DW images and ADC maps. Some studies reported that the reproducibility for ADC and IVIM measurement of hepatic nodules was poor [27][28][29].…”
Section: Discussionsupporting
confidence: 78%